2021
DOI: 10.3389/fphar.2020.608672
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activities of Echinops kebericho Mesfin Tuber Extracts and Isolation of the Most Active Compound, Dehydrocostus Lactone

Abstract: Echinops kebericho Mesfin is traditionally used for the treatment of various infectious diseases. This study investigated antibacterial activity of the essential oil (EO) and the different fractions of ethanol extract. The most active component was isolated and identified. Isolation and purification was accomplished using chromatographic techniques while identification was done by spectroscopic method. Minimum inhibitory concentration (MIC) was determined using the broth micro-dilution method. In bioactive-gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The essential oil obtained from this plant exhibited mosquito repellent and larvicidal activity ( Debela et al, 2007 ; Jemberie et al, 2016 ). Deyno et al have shown that the tuber extract of this medicinal plant in five different solvents showed variable MIC concentration against eight bacterial species ( Deyno et al, 2020b ). In the same study they have also shown the antibacterial activity of essential oil of extracted from E. kebericho Mesfin against eight bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The essential oil obtained from this plant exhibited mosquito repellent and larvicidal activity ( Debela et al, 2007 ; Jemberie et al, 2016 ). Deyno et al have shown that the tuber extract of this medicinal plant in five different solvents showed variable MIC concentration against eight bacterial species ( Deyno et al, 2020b ). In the same study they have also shown the antibacterial activity of essential oil of extracted from E. kebericho Mesfin against eight bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…In most of the preparation of the ethnomedicinal medicines, the root of the plant is mostly used and in some cases the bulb and the stem are used (Bitew and Hymete, 2019). The safety of Echinops kebericho Mesfin has been seen in animal models (Deyno et al, 2020a). Several phytochemical screening studies carried out on E. kebericho Mesfin have shown the presence of flavonoids, alkaloids, triterpenoids, saponins and steroids in the in the essential oil extracted from the roots (Abegaz et al, 1991;Toma et al, 2015).…”
Section: Pharmacological Properties and Bioactivities Of The Asterace...mentioning
confidence: 99%
“…To do this, the crude extract was double-diluted to provide a spectrum of concentrations that were all twice as concentrated as previously. Making a stock solution was the first step, and sterilized nutrient/brain heart infusion broth was used to dilute each crude extract made from stock solutions [ 66 ].…”
Section: Methodsmentioning
confidence: 99%
“…Echinops kebercho is a multipurpose traditional medicinal plant confined to Ethiopia in distribution (Tadesse, 2004 ; Figure 1 ). It is used to treat various infectious diseases, and bioactive extracts of E. kebericho have antibacterial activities (Deyno et al, 2021 ; Fikadu & Melesse, 2014 ; Tariku & Kebede, 2011 ; Toma et al, 2015 ). The extracts of its rootstock cure epilepsy, epistaxis, atrophy, and sudden sickness (Maryo et al, 2015 ), exhibit high anti‐Leishmanial activity (Tariku et al, 2011 ), and can be used to control insect pests of medical, veterinary, and agricultural values (Hussien et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%